Alginate-Capped Silver Nanoparticles as a Potent Anti-mycobacterial Agent Against Mycobacterium tuberculosis - Chen, Cheng-Cheung; Chen, Yih-Yuan; Yeh, Chang-Ching; Hsu, Chia-Wei; Yu, Shang-Jie; Hsu, Chih-Hao; Wei, Ting-Chun; Ho, Sin-Ni; Tsai, Pei-Chu; Song, Yung-Deng; Yen, Hui-Ju; Chen, Xin-An; et al. (Frontiers in Pharmacology, 2021)
Tuberculosis (TB) is a leading cause of death from a single infectious agent, Mycobacterium tuberculosis (Mtb). Although progress has been made in TB control, still about 10 million people worldwide develop TB annually and 1.5 million die of the disease. The rapid emergence of aggressive, drug-resistant strains and latent infections have caused TB to remain a global health challenge. TB treatments are lengthy and their side effects lead to poor patient compliance, which in turn has contributed to the drug resistance and exacerbated the TB epidemic. The relatively low output of newly approved antibiotics has spurred research interest toward alternative antibacterial molecules such as silver nanoparticles (AgNPs). In the present study, we use the natural biopolymer alginate to serve as a stabilizer and/or reductant to green synthesize AgNPs, which improves their biocompatibility and avoids the use of toxic chemicals. The average size of the alginate-capped AgNPs (ALG-AgNPs) was characterized as nanoscale, and the particles were round in shape and of similar size distribution. Drug susceptibility tests showed that these ALG-AgNPs are effective against both drug-resistant Mtb strains and dormant Mtb. A bacterial cell-wall permeability assay showed that the anti-mycobacterial action of ALG-AgNPs is mediated through an increase in cell-wall permeability. Notably, the anti-mycobacterial potential of ALG-AgNPs was effective in both zebrafish and mouse TB animal models in vivo. These results suggest that ALG-AgNPs could provide a new therapeutic option to overcome the difficulties of current TB treatments.